ASEAN-NEPAD partnership: Towards advancement and making a difference - Terwase, Isaac Terungwa; Ibrahim, Muhammad Bello; Abdul Talib, Asmat Nizam; Yerima, Hindatu Maigari (2016)
The African continent is endowed with natural, agricultural and human resources, yet when compared to other continents of the world, in terms of development and growth, the continent is still left behind. In this notion, African leaders through their regional organization known as African Union established the New Partnership for Africa’s Development (NEPAD) which sought to partner with African countries and other countries of the world with a view of engaging into programs that would develop the continent. As such, NEPAD partnership with the Association of South-East Asian Nations (ASEAN) is targeted at exploring the opportunities in Africa towards the advancement of the continent and, in turn, providing a new ground for ASEAN in achieving her targeted sub-regional economic development. This research paper seeks to explore the opportunities in this partnership where ASEAN countries can benefit from Africa and vice-visa. The research made use of qualitative approach through the conduct of interviews, review of previous literature, internet sources, academic journals and use of available books as sources of data collection. The findings from this research reveals that most of Africa’s resources are yet to be tapped; areas such as science and technology, agriculture, transport system, telecommunications, and development of natural resources are key areas where ASEAN countries can invest in through partnership with the NEPAD program implementation. As such, a new ground for ASEAN countries to move in.